Mathematical methodologies for the measurement of the quality of education in engineering programs in Peru - Nieto Chaupis, Huber (2017)
It's well known that the duration of the engineering programs in Latin American countries like Peru are of order of 5 years, roughly. Commonly, the target of the fifth year of program is to carry out activities of thesis and capstone projects. Clearly these activities would demand that the student can exhibit skills and a certain level of maturity which might be crucial for a successful completion of the projects. However, the expected performance of the students might be correlated to the educational features of the institution (university, technological institute, etc) to some extent. In this manner, in this paper we try to measure the quality of education (QoE) of a Peruvian engineering program through the application of a mathematical methodology based on the individual score of students along the time where the projects take place. Furthermore, the error of the model is interpreted as the possible ambiguities in the evaluations of the progress of the projects, which in some cases the model fails. The present methodology has been applied in a private university in Lima city with data from the 2016, resulting the QoE = 0.65 or 65% and its error in the order of 8.39%.